Bioprocess Design: The GEOGAS Project: Bioremediation of geothermal gases and SCP production with HOX/SOX bacteria - Monit, Michał (2009)
RES Master´s Thesis Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri Bioprocess engineering is a field of science which lately has been experiencing huge growth. Progress in genetic engineering and microbiology, as well as engineering improvements, allow to overcome the limits, both technical and economical, experienced by industrial processes as recently as ten years ago. Still, bioprocess design and scale-up are highly interdisciplinary fields which rely heavily on previous work in the area. However, for novel processes, there is not much relevant research, which makes the introduction of new bioprocesses challenging. One such case is the GEOGAS project, which aims at utilization of sulfur- (SOX) and hydrogen-oxidizing (HOX) bacteria for simultaneous abatement of hydrogen sulfide and carbon dioxide from geothermal power plants and production of single-cell proteins (SCP). In this work bioprocess design (and engineering) principles are introduced to provide a GEOGAS-oriented framework for tackling new process introduction and scale-up. Further on, in the case study of the Project, the focus is placed on determining crucial factors and issues which could possibly be encountered during scale-up. The obtained results show that the current shape of the design is not yet satisfactory; however, it presents a possibly big gap for tackling numerous pollution and waste disposal problems. Finally, a brief discussion on possible project follow-up and development is presented.